1999
DOI: 10.1016/s1097-2765(00)80332-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Major Intestinal Fatty Acid Transport Protein

Abstract: While intestinal transport systems for metabolites such as carbohydrates have been well characterized, the molecular mechanisms of fatty acid (FA) transport across the apical plasmalemma of enterocytes have remained largely unclear. Here, we show that FATP4, a member of a large family of FA transport proteins (FATPs), is expressed at high levels on the apical side of mature enterocytes in the small intestine. Further, overexpression of FATP4 in 293 cells facilitates uptake of long chain FAs with the same speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
312
3
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(337 citation statements)
references
References 40 publications
(9 reference statements)
16
312
3
6
Order By: Relevance
“…Primary hepatocytes were prepared by two-step perfusion with liver perfusion and digestion medium, according to the manufacturer's instructions (Invitrogen), and were immediately used for uptake assays. Fluorescence-activated cell sorter-based short-term (30 sec) FA uptake assays were performed as described (24).…”
Section: Glucose Tolerance Test (Gtt)mentioning
confidence: 99%
“…Primary hepatocytes were prepared by two-step perfusion with liver perfusion and digestion medium, according to the manufacturer's instructions (Invitrogen), and were immediately used for uptake assays. Fluorescence-activated cell sorter-based short-term (30 sec) FA uptake assays were performed as described (24).…”
Section: Glucose Tolerance Test (Gtt)mentioning
confidence: 99%
“…Although fatty acids are hydrophobic and are capable of rapidly diffusing through the lipid bilayer when present in high concentrations [41], a large body of evidence supports the presence of a protein-mediated carrier system that operates at low substrate concentrations [24,42]. I-FABP and FATP4 are thought to be key factors for long-chain fatty acid uptake in enterocytes [24,25], whereas NPC1L1 is thought to play a critical role in intestinal cholesterol absorption [26,27]. Our present results demonstrate that isoleucine and whey downregulated the expression of i-FABP, FATP4, and NPC1L1, with a plateau at 2.0% concentration corresponding to about 65% inhibition of i-FABP, 60% of FABP, and 70% of NPC1L1.…”
Section: Discussionmentioning
confidence: 99%
“…Three key transcription factors, designated sterol regulatory element binding proteins (SREBPs) 1a, 1c, and 2, regulate the transcription of genes involved in fatty acid and cholesterol synthesis including acetyl-coenzyme A carboxylase (ACC), fatty acid synthase (FAS), and 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) [23]. In addition, intestinal-type fatty acid binding protein (i-FABP) and fatty acid transport protein-4 (FATP4) are thought to be important factors for long-chain fatty acid uptake in enterocytes [24,25], whereas Niemann-Pick C-1-like-1 protein (NPC1L1) is thought to be the principal intestinal cholesterol transporter [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…However, the expression was significantly reduced in the jejunum (fc: 21.87, DON5). In primary enterocytes treated with SLC27A4 antisense, palmitate and oleate uptake were reduced simultaneously (Stahl et al, 1999). Maresca et al (2002) reported an increased palmitate uptake by 35% in their study after challenging HT-29-D4 cells with DON.…”
Section: Nutrient Transportmentioning
confidence: 91%